Designing Incident Management Standard Operating Procedures at XYZ Hospital based on the ITIL V3 Framework - Putri, Syachla Malikha; Mukaromah, Siti; Pratama, Arista (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Minister of Health Regulation No.82 of 2013 stipulates that every hospital must implement SIMRS, based on this regulation, XYZ Hospital implements information technology in the form of SIMRS. XYZ Hospital provides an SOP for the Hospital Management Information System (SIMRS) that guides the Management Information Systems Unit in managing SIMRS issues or incidents. However, the current SOP is not yet aligned with the best practices in ITIL, not all reports related to SIMRS incidents are recorded, which leads to inaccuracies in the information received by the parties involved in handling the SIMRS incidents. Therefore, this research was created to design an incident management SOP document based on the ITIL V3 framework because it includes detailed activities regulating how to handle IT service incidents properly. GAP analysis method was used to map the current conditions of the incident SIMRS management process to ideal conditions according to ITIL V3. The results of this research are an incident management SOP document accompanied by supporting documents in proper forms that make it easier to carry out activities in the SOP. The design of an incident management SOP by the ITIL framework can serve as a reference, improve performance, and provide convenience for the functional units of XYZ Hospital in handling SIMRS issues more systematically and aligned with best practices in IT service management.